Ethnobotanical study of Hammada scoparia (Pomel) Iljin in the region of Naâma (south-western Algeria) - Boucherita H (Arabian Journal of Medicinal and Aromatic Plants, 2018)
The Hammada scoparia is a relatively common and characteristic steppe species of the Saharan Atlas of south-western Algeria. It has several ecological, medicinal and floristic interests. The description of its ethnobotany in the region of Naâma will contribute to a better knowledge and valorization of this species. An ethnobotanical survey was carried out using 100 questionnaires undertaken from October 2014 to September 2015 with users, herbalists, traditional healers and the local population of Naâma. The exploitation of the results of the ethnobotanical survey made it possible to identify the different ways of using and exploiting Hammada scoparia. More than 45% of the population uses this plant against poisonous reptile bites such as scorpions, snakes and vipers as well as the treatment of digestive tract diseases, injuries, skin inflammations and diabetes. The species Hammada scoparia is a perennial chamaephytic plant with many therapeutic virtues, the most important of which remains its action in the treatment of scorpion stings.